PREPARE: protocol for a stepped wedge trial to evaluate whether a risk stratification model can reduce preterm deliveries among women with suspected or confirmed preterm pre-eclampsia - Bastos Dias, Marcos Augusto; De Oliveira, Leandro [UNESP]; Jeyabalan, Arundhanthi; Payne, Beth; Redman, Christopher W.; Magee, Laura; Poston, Lucilla; Chappell, Lucy; Seed, Paul; von Dadelszen, Peter; Roberts, James Michael; PREPARE Res Grp (Bmc, 2019)
Background Preeclampsia (PE) is a major cause of short and long-term morbidity for affected infants, including consequences of fetal growth restriction and iatrogenic prematurity. In Brazil, this is a special problem as PE accounts for 18% of preterm births (PTB). In the PREPARE (Prematurity REduction by Pre-eclampsia cARE) study, we will test a novel system of integrated care based on risk stratification and knowledge transfer, to safely reduce PTB. Methods This is a stepped wedge cluster randomised trial that will include women with suspected or confirmed PE between 20 + 0 and 36 + 6 gestational weeks. All pregnant women presenting with these findings at seven tertiary centres in geographically dispersed sites, throughout Brazil, will be considered eligible and evaluated in terms of risk stratification at admission. At randomly allocated time points, sites will transition to risk stratification performed according to sFlt-1/PlGF (Roche Diagnostics) measurement and fullPIERS score with both results will be revealed to care providers. The healthcare providers of women stratified as low risk for adverse outcomes (sFlt-1/PlGF <= 38 AND fullPIERS< 10% risk) will receive the recommendation to defer delivery. sFlt-1/PlGF will be repeated once and fullPIERS score twice a week. Rates of prematurity due to preeclampsia before and after the intervention will be compared. Additionally, providers will receive an active program of knowledge transfer about WHO recommendations for preeclampsia, including recommendations regarding antenatal corticosteroids for foetal benefits, antihypertensive therapy and magnesium sulphate for seizure prophylaxis. This study will have 90% power to detect a reduction in PTB associated with PE from a population estimate of 1.5 to 1.0%, representing a 33% risk reduction, and 80% power to detect a reduction from 2.0 to 1.5% (25% risk reduction). The necessary number of patients recruited to achieve these results is 750. Adverse events, serious adverse events, both anticipated and unanticipated will be recorded. Discussion The PREPARE intervention expects to reduce PTB and improve care of women with PE without significant adverse side effects. If successful, this novel pathway of care is designed for rapid translation to healthcare throughout Brazil and may be transferrable to other low and middle income countries.
Keywords: Pre-eclampsia; Preterm birth; Prematurity; sFlt-1; PlGF; fullPIERS